Pengembangan dan Pemanfaatan Media Pembelajaran Fun Indonesian Folktales Pada Pembelajaran Bahasa Inggris Siswa Kelas X SMA Negeri 1 Negara - Krisnayanti, Iga Ayu Anggela Heni; Pramono, Rudy (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The objective of this research was to create a Fun Indonesian Folktales learning medium to be utilized to teach English for the Grade X students at the Senior High School of 1 Negara. The Research and Development (RnD) method was used in this research, according to (Borg and Gall 2003). The researchers modified and simplified it into 9 adjusted cycles. The interviews and questionnaires were used to collect data, which were then analyzed qualitatively and quantitatively. Three tryouts were conducted three times during the product development process: initial tryout, field tryouts, and field implementation tryout. VR expert, pedagogy expert, material expert, and an English translation were all involved in the initial tryout. Five students participated in the field tryout. Seventeen students participated in the field implementation tryout. The experts and students were allowed to try the product and respond to the provided questionnaire. According to the final data analysis, the attractiveness of the interactive media was 93.5%, the level of practicality was 94.8%, and the student learning motivation was 94.3%. As a result, the product being developed is feasible and has shown the potential to be used as a new medium in the English subjects.